Prognostic Role of Circulating miR-141 in Early Diagnosis of Colorectal Cancer - Merve Simsek Dilli; Ertugrul Bayram; Ismail Oguz Kara (Medicina)
Background: Colorectal cancer (CRC) is the second leading cause of cancer-related deaths worldwide, emphasizing the urgent need for reliable biomarkers for early diagnosis and prognosis. MicroRNA-141 (miR-141) is a small non-coding RNA molecule that plays a regulatory role in cell proliferation and differentiation and has been linked to various types of cancer. Objective: This study aims to evaluate the clinical and prognostic relevance of circulating levels of miR-141 in untreated patients with CRC. Method: A total of 40 patients with CRC and 20 healthy subjects matched for age and sex were selected for this study. Blood samples from these individuals were analyzed using real-time PCR to determine the levels of miR-141. Results: Despite the absence of any substantial correlations between levels of miR-141 and conventional prognostic factors, including disease stage, lymph node involvement, vascular/perineural invasion, or metastasis, a statistically significant correlation was identified between miR-141 levels and the extent of local tumor invasion (T stage) (p = 0.034). These findings suggest that microRNA-141 may be involved in local tumor infiltration and warrant further validation in larger, multicenter studies. Conclusions: Although miR-141 alone may not serve as a definitive biomarker for CRC diagnosis or prognosis, its potential role—particularly in combination with other markers—could contribute to refined risk stratification strategies in CRC management.